국가연구개발사업 관리자의 성과정보 활용에 영향을 미치는 요인 - 유나리; Nari Yoo (국정관리연구, 2024)
정부는 국가연구개발사업 성과평가가 ‘평가를 위한 평가’가 아닌 사업 개선과 성과 제고에 기여하도록 하는 방안을 모색하고 있다. 이에 연구관리 현장에서 성과정보의 활용을 지원할 필요가 있으며, 이를 위해 조직 내부의 성과정보 활용 메커니즘을 이해하는 것이 필요하다. 본 연구는 성과정보의 활용에 영향을 미치는 요인으로 이해관계자의 참여에 주목하였고, 이해관계자 참여가 성과정보의 품질에 대한 인식을 제고함으로써 성과정보의 활용을 증가시키는 매개효과 모형을 설정하였다. 실증분석을 위하여 과학기술정책연구원에서 수행한 ‘R&D 성과평가 정보 활용 실태조사(2022년)’ 결과를 활용하였으며, 3단계 다중회귀분석을 수행하였다. 분석결과, 이해관계자의 참여는 이해 및 개선 목적의 성과정보 활용에 직접적인 영향을 미칠 뿐만 아니라 성과정보의 품질에 대한 인식 제고를 통해 간접적인 영향도 미친다는 점을 확인하였다. 이는 R&D분야 성과정보 활용과 관련한 이론적, 정책적 시사점을 제공한다. The government is seeking ways to ensure that performance evaluations of national R&D programs contribute to program improvement and enhanced outcomes, rather than being mere "evaluations for evaluation's sake." Therefore, it is necessary to support the use of performance information in research management, and understanding the mechanisms for using performance information within organizations is essential. This study focuses on stakeholder involvement as a factor affecting the use of performance information, and establishes a mediation model where stakeholder participation enhances the perception of the quality of performance information, thereby increasing its utilization. For empirical analysis, the study uses data from the "Survey on the Utilization of R&D Performance Evaluation Information (2022)" conducted by the Science and Technology Policy Institute, and performs a three-step multiple regression analysis. The analysis results confirms that stakeholder involvement not only directly affects the use of performance information for understanding and improvement purposes, but also indirectly affects it by enhancing the perception of the quality of performance information. This provides theoretical and policy implications for the use of performance information in the R&D field.